Utilization Of Malaysian Aroids For Medicinal Purposes. - Sulaiman, Baharuddin; Mansor, Mashhor (Universiti Sains Malaysia, 2001)
The aroid family or also known as Araceae, is generally a tropical plant, however some of the species are distributed worldwide. This family is grouped into nine subfamilies, 106 genera and 3200 species.